Rancang Bangun Aplikasi E-Sertifikat Berbasis Web pada DPK Apindo Kota Cirebon - Syafiq, Mohammad Sayyid; Hamonangan, Ryan; Dana, Raditya Danar; Tohidi, Edi; Hayati, Umi (LPPM UNIKA Santo Thomas Medan, 2022)
DPK APINDO Kota Cirebon is an association consisting of Entrepreneurs and or Companies domiciled in Cirebon City. Every member registered with DPK APINDO Kota Cirebon has a certificate as proof that the company has become a member. However, the creation of this membership certificate is still manual so that in the creation of the certificate takes a long time and is inefficient, for that the author tries to make the final task regarding the e-certificate application of membership in DPK APINDO Kota Cirebon. In solving this problem, the author designing the application uses prototype development methods. E-certificate membership application was created based on the website in DPK APINDO Kota Cirebon by using the PHP programming language with mysql as a database and And FPDF is a PHP library that serves as converting PHP syntax into PDF.